Role Of Green Open Space In Performance Improvement Of Malang City Center - subhan ramdlani; Lisa Dwi Wulandari (Journal of Innovation and Applied Technology, 2018)
This study is a continuation of previous research [5],[6],[7], on the hierarchy of the Green Open Space’s role of the city based on its 9 classifications (Green Line, City Park, Urban forest, Garden Tomb, Sports Park, Rotonde, Monument Park, Playground, and Offices Park) in improving the ecological quality of Malang city center. The focus of this research is to create an eco-quality ideal RTH arrangement model, especially Green Open Spaces which has the biggest role in improving the performance of downtown Malang. The arrangement considers several factors, namely: first, environmental-ecological factors related to environmental emission levels, air temperature and humidity [5],[6],[7]. Second, the physical environment of Green Open Spaces has a setting factor which includes all the hardscape element forming attributes and softscape elements. Third, the human activity factor, which uses the physical environment setting as a container to perform various activities. The advantage of this study lies in the process technology, which is in the process of arrangement of Green Open Spaces in the field of architectural science (with a qualitative method approach based on the designer's intuitive concept), so in this study the approach is precisely on the quantitative study, with statistical measurement, the results are processed through Graphics and tabulation systems and utilizing City CAD software in simulation and Green Open Space’s exploration in downtown Malang.